2018
DOI: 10.1186/s40168-018-0565-6
|View full text |Cite
|
Sign up to set email alerts
|

Ecologically informed microbial biomarkers and accurate classification of mixed and unmixed samples in an extensive cross-study of human body sites

Abstract: BackgroundThe identification of body site-specific microbial biomarkers and their use for classification tasks have promising applications in medicine, microbial ecology, and forensics. Previous studies have characterized site-specific microbiota and shown that sample origin can be accurately predicted by microbial content. However, these studies were usually restricted to single datasets with consistent experimental methods and conditions, as well as comparatively small sample numbers. The effects of study-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 51 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…We also found MVs to be interesting in their own right: in our HMP analysis, they constituted central nodes in the association network with many directly associated OTUs, in line with the expected habitat preference of many microbes (The Human Microbiome Project Consortium 2012) and known primer biases (Tremblay et al, 2015). Consistent with these results, closely related approaches have previously identified parsimonious sets of predictive microbial biomarkers for human body sites and a skin disease (Tackmann et al, 2018;Statnikov et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…We also found MVs to be interesting in their own right: in our HMP analysis, they constituted central nodes in the association network with many directly associated OTUs, in line with the expected habitat preference of many microbes (The Human Microbiome Project Consortium 2012) and known primer biases (Tremblay et al, 2015). Consistent with these results, closely related approaches have previously identified parsimonious sets of predictive microbial biomarkers for human body sites and a skin disease (Tackmann et al, 2018;Statnikov et al, 2013).…”
Section: Discussionsupporting
confidence: 81%
“…For instance, Hanssen et al [14] showed that a combination of principal component analysis (PCA) and linear discriminant analysis (LDA) can successfully be used to differentiate samples from saliva being deposited on skin and samples of skin only. In addition, Tackmann et al [43] have shown that machine learning algorithms trained on large heterogeneous datasets provide high accuracy when predicting body fluids, not only from single source samples but also from mixtures generated in-silico. In another study, Hanssen et al [15] developed a prediction model using partial least squares (PLS) in combination with LDA using data from the Human Microbiome Project for the identification of samples originating from the oral, nasal and vaginal cavity as well as skin and feces.…”
Section: Introductionmentioning
confidence: 99%
“…2017) (although the authors report a clean negative control) and sometimes pure in-silico studies might identify contaminations as biologically relevant (Tackmann et al . 2018). These examples come in addition to further publications mentioned in (de Goffau et al .…”
Section: Introductionmentioning
confidence: 99%